2022
DOI: 10.1371/journal.pone.0276913
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and diabetes co-occurrence: A national study with 44 million person-years of follow-up

Abstract: The number of new cases of cancer is increasing each year, and rates of diabetes mellitus are also increasing dramatically over time. It is not an unusual occurrence for an individual to have both cancer and diabetes at the same time, given they are both individually common, and that one condition can increase the risk of the other. In this manuscript, we use national-level diabetes (Virtual Diabetes Register) and cancer (New Zealand Cancer Registry) data on nearly five million individuals over 44 million pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Diabetes is a multisystem disorder that is associated with a greater risk of getting breast cancer 7–10 . In Aotearoa/New Zealand, the rate of breast cancer is approximately 15% higher among those with diabetes than people without diabetes 10 . Patients with diabetes often have worse tumor characteristics at cancer diagnosis, and poorer outcomes when compared to patients without diabetes 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is a multisystem disorder that is associated with a greater risk of getting breast cancer 7–10 . In Aotearoa/New Zealand, the rate of breast cancer is approximately 15% higher among those with diabetes than people without diabetes 10 . Patients with diabetes often have worse tumor characteristics at cancer diagnosis, and poorer outcomes when compared to patients without diabetes 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a multisystem disorder that is associated with a greater risk of getting breast cancer 7–10 . In Aotearoa/New Zealand, the rate of breast cancer is approximately 15% higher among those with diabetes than people without diabetes 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to non-diabetic individuals, patients with type 2 diabetes have an increased risk and worse prognosis for BTC [ 10 , 11 , 12 ]. Recent studies have also found that the prevalence and co-occurrence of diabetes is higher in digestive cancers [ 13 , 14 ]. Metformin is often used as the first-line treatment for type 2 diabetes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies and observations in the field of overseas studies have confirmed this view. It is reported that among patients with type 2 diabetes, the relative risk of endometrial cancer, liver cancer and pancreatic cancer is more than 2 times, while the relative risk of bladder cancer, breast cancer and colorectal cancer is as high as 1.5 times (9)(10)(11)(12). In addition to the increase in incidence rate, the overall mortality rate of diabetes patients when diagnosed with cancer is higher (13) than that of the non-disease group.…”
Section: Introductionmentioning
confidence: 99%